INCLUSÃO DIGITAL E FINANCEIRA PELO M-BANKING COMO OPORTUNIDADE DE NEGÓCIOS PARA UM BANCO DIGITAL: O CASO DA CAIXA ECONÔMICA FEDERAL E A ACEITAÇÃO E USO DO APLICATIVO CAIXATEM - Santos, Gilmar Veriato Fluzer dos (2022)
This study aimed to analyze the factors that influence the acceptance and use of m-banking and CaixaTem application for financial services, and whether they allow Caixa Econômica Federal to create an inclusive and sustainable Digital Bank. To this end, a field research was carried out with 300 respondents in the city of Cascavel/PR, whose instrument made it possible to apply statistical-descriptive methods, factor regression analysis and models to reach the objectives and results. The theoretical basis of the research was the Unified Theory of Acceptance and Use of Technology – UTAUT, duly tested and consolidated in the literature, by using the variables (constructs) performance expectancy, social influence, perceived credibility, perceived financial cost, facilitating conditions and behavioral intention and its influence on the behavior of use. The results found lead to the conclusion that all constructs in the model had their hypotheses accepted in their relationships, with the exception of the variable perceived credibility, which showed no significant influence on the intention to use construct. Furthermore, it was possible to confirm the timeliness of creating a Digital Bank (fintech) for the institution, due to the fact that CaixaTem represents an asset already in operation and with a potentially profitable base, although the results obtained in the intention to use are higher than the actual use of the application. The digital and financial inclusion of the low-income public was also promising, especially if one considers its massive customer base, the potential for expansion of inactive accounts and the offer of microcredit to the population, especially for consumption, despite its underutilization and operational limitations in this market, as shown by the results of the model analysis.